Differential effects of Cl- and SO42- anion systems on Ca2+-Mg2+-Mn2+ carbonate biomineralization induced by the halophilic Bacillus dokdonensis: Implications for Mn2+-containing saline wastewater treatment - Xueting Chen; Yueming Zhao; Hui Zhao; Memon Kashif Ali; Ran Shu; Bo Liu; Boyu Cai; Runxi Yin; Zuozhen Han; Huaxiao Yan (Journal of Hazardous Materials, 2026)

Temporal-spatial characteristics of surface cracks during landslide evolution - Pengju An; Qinglu Deng; Yueming Yin; Weibo Li; Kai He; Kun Fang (Engineering Geology, 2026)

Arbuscular mycorrhizal symbiosis enhances microbial contribution to mineral-associated organic carbon persistence in soil: Insights from soil microbial community and microbial necromass carbon - Yin LIU; Jin QIAN; Yueming ZHU; Jing HU; Bianhe LU; Yuxuan HE; Junwei SHEN (Pedosphere, 2026)

Does algal trophic mode affect the removal of norfloxacin? Insights from Tetradesmus obliquus - Musheng Ji; Jin Qian; Xiaxia Li; Yueming Zhu; Yin Liu; Bianhe Lu; Sijing Tang; Junwei Shen; Yuhang Zong (Journal of Hazardous Materials, 2026)

The combined exposure to antibiotics intensified the phytotoxicity of perovskite composite nanoparticles to Phragmites communis - Yuxuan He; Yueming Zhu; Jin Qian; Bianhe Lu; Sijing Tang; Yin Liu; Junwei Shen; Musheng Ji (Journal of Environmental Management, 2026)

Corrigendum to “Simultaneous removal of Mn²⁺ and Sr²⁺ from wastewater via microbially induced carbonate precipitation (MICP) using immobilized Bacillus licheniformis K-1: A sustainable bioremediation approach” [J Hazard Mater 501 (2026) 14065] - Kashif Ali Memon; Huaxiao Yan; Muhammad Mujahid; Jiabin Geng; Shuqi Wang; Runxi Yin; Yueming Zhao; Akash Kumar; Azhar Ali Laghari; Zuozhen Han; Na Guo; Hui Zhao (Journal of Hazardous Materials, 2026)

Simultaneous removal of Mn²⁺ and Sr²⁺ from wastewater via microbially induced carbonate precipitation (MICP) using immobilized Bacillus licheniformis K-1: A sustainable bioremediation approach - Memon Kashif Ali; Huaxiao Yan; Muhammad Mujahid; Jiabin Geng; Shuqi Wang; Runxi Yin; Yueming Zhao; Akash Kumar; Azhar Ali Laghari; Zuozhen Han; Na Guo; Hui Zhao (Journal of Hazardous Materials, 2026)

Corrigendum to “Jasmonate activates PuMYC2 and decreases histone acetylation levels to inhibit the ester aroma catabolism in cold-stored Nanguo pears fruit” [Postharvest Biol. Technol. 224 (2025) 113466] - Liyong Qi; Nannan Zang; Juntong Jin; Weiting Liu; Xiaojing Li; Yueming Yang; Baofeng Wang; Zepeng Yin; Aide Wang (Postharvest Biology and Technology, 2025)

Homoeologous recombination-based transfer and cytological mapping of the novel powdery mildew resistance gene Pm7C from Aegilops caudata - Yueming Ren; Mengzhen Luo; Yajun Feng; Qifan Chen; Chao Ma; Wenxuan Liu; Fu Guo; Qianwen Liu; Muhammad Amjad; Ranran Jia; Xinpei He; Xiang Ji; et al. (Theoretical and Applied Genetics, 2025)

Polystyrene nanoplastics reshape the peatland plants (Sphagnum) bacteriome under simulated wet-deposition pathway: Insights into unequal impact of ecological niches - Sijing Tang; Jin Qian; Yueming Zhu; Bianhe Lu; Yuxuan He; Yin Liu; Kailin Xu; Junwei Shen (Journal of Hazardous Materials, 2025)

Jasmonate activates PuMYC2 and decreases histone acetylation levels to inhibit the ester aroma catabolism in cold-stored Nanguo pears fruit - Liyong Qi; Nannan Zang; Juntong Jin; Weiting Liu; Xiaojing Li; Yueming Yang; Baofeng Wang; Zepeng Yin; Aide Wang (Postharvest Biology and Technology, 2025)

Interaction between root exudates and PFOS mobility: Effects on rhizosphere microbial health in wetland ecosystems - Bianhe Lu; Peifang Wang; Yueming Zhu; Jing Hu; Jin Qian; Yuanyuan Huang; Junwei Shen; Sijing Tang; Yin Liu (Environmental Pollution, 2025)

Review the antioxidant and angiotensin converting enzyme inhibitory peptides derived from fish: Preparation, structure-relationship, bioavailability and ameliorating strategies - Shu Wang; Lu Zhang; Hui Wang; Bizhen Zhong; Yueming Hu; Hongmei Yin; Zongcai Tu (Food Bioscience, 2024)

Citrus exosome-modified exogenous dsRNA delivery reduces plant pathogen resistance and mycotoxin production - Chunxiao Yin; Yuli Lao; Lihong Xie; Lianfei Chen; Yueming Jiang; Liang Gong (Pesticide Biochemistry and Physiology, 2024)

An Obstacle Avoidance Strategy for AUV Based on State-Tracking Collision Detection and Improved Artificial Potential Field - Yueming Li; Yuhao Ma; Jian Cao; Changyi Yin; Xiangyi Ma (Journal of Marine Science and Engineering, 2024)
This paper proposes a fusion algorithm based on state-tracking collision detection and the simulated annealing potential field (SCD-SAPF) to address the challenges of obstacle avoidance for autonomous underwater vehicles (AUVs) in dynamic environments. Navigating AUVs in complex underwater environments requires robust autonomous obstacle avoidance capabilities. The SCD-SAPF algorithm aims to accurately assess collision risks and efficiently plan avoidance trajectories. The algorithm introduces an SCD model for proactive collision risk assessment, predicting collision risks between AUVs and dynamic obstacles. Additionally, it proposes a simulated annealing (SA) algorithm to optimize trajectory planning in a simulated annealing potential field (SAPF), integrating the SCD model with the SAPF algorithm to guide AUVs in obstacle avoidance by generating optimal heading and velocity outputs. Extensive simulation experiments demonstrate the effectiveness and robustness of the algorithm in various dynamic scenarios, enabling the early avoidance of dynamic obstacles and outperforming traditional methods. This research provides an accurate collision risk assessment and efficient obstacle avoidance trajectory planning, offering an innovative approach to the field of underwater robotics and supporting the enhancement of AUV autonomy and reliability in practical applications.

Insight into the crack characteristics and mechanisms of retrogressive slope failures: A large-scale model test - Yueming Yin; Qinglu Deng; Weibo Li; Kai He; Zhenghong Wang; Haijun Li; Pengju An; Kun Fang (Engineering Geology, 2023)

H2O2-activated transcription factor MdERF4 negatively regulates ethylene biosynthetic during fruit ripening by suppressing MdACS1 transcription - Nannan Zang; Xiaojing Li; Liyong Qi; Zhuoran Zhang; Yueming Yang; Zepeng Yin; Aide Wang (Postharvest Biology and Technology, 2023)

Revealing the crystal phase effect of CeO2 in spinel-based nanocatalysts toward the peroxymonosulfate activation for organics degradation - Yuxuan He; Yueming Zhu; Jin Qian; Peifang Wang; Yuhang Zhang; Kailin Xu; Bianhe Lu; Yin Liu; Junwei Shen (Chemical Engineering Journal, 2023)

Involvement of miRNAs-mediated senescence and salicylic acid defense in postharvest litchi downy blight - Chunxiao Yin; Lihong Xie; Yanfei Wu; Hongxia Qu; Bao Yang; Liang Gong; Yueming Jiang; Taotao Li (Food Chemistry, 2023)

DEM-CFD investigation on the effects of angularity and roughness on the mass loss of soil rock mixtures - Fan Chen; Yingchao Wang; Wen Jiang; Yin Guo; Yueming Wang (European Journal of Environmental and Civil Engineering, 2022)